(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The role of modern technologies and interactive methods in improving classroom management efficiency has become one of the most discussed and highly relevant topics in the field of educational sciences. In the contemporary educational context, the classroom is no longer seen as a space where only one-sided communication occurs or where the teacher is the sole source of knowledge and authority. Instead, with the advancement of modern technologies and the implementation of interactive teaching methods, a new dimension of communication, cooperation, and efficient classroom management has emerged. Educators of the current era are required to adapt and integrate these technologies and interactive methods to respond to the changing needs and interests of students as well as to increase the overall effectiveness of the teaching and learning process.